Annonaceae dari Wawonii, Sulawesi Tenggara Annonaceae from Wawonii Island, South East Sulawesi - Rugayah, Rugayah (JURNAL BIOLOGI INDONESIA, 2014)
Wawonii Island is one of small islands located in the southeast of Sulawesi, with an area of approximately 6500km2. Exploration activities and inventories have been conducted in the year 2003-2006, more than 900 plantspecies have been identified, including fern and cultivated plants. Annonaceae included one of the families foundin this area. Ten species were listed belongs to 8 genera, namely Anaxagorea (A. cf. luzonensis A. Gray), Annona (A.muricata L., A.squamosa L.), Artabotrys (A. suaveolens (Blume) Blume), Cananga (C.odorata (Lam .) Hook.f.,&Thomson), Monoon (Monoon sp.), Polyalthia (P. celebica Miq.), Pseuduvaria (P. reticulata (Blume) Miq. andUvaria (U. littoralis (Blume) Blume, Uvaria sp.). One species of its Pseuduvaria reticulata as a new record forSulawesi. Identification keys to the genera, and its distribution will be discussed in the paper.Keywords: Annonaceae, Wawonii island, S.E. Sulawesi